High relaxivity Gd3+-based organic nanoparticles for efficient magnetic resonance angiography - Zhuang Liu; Menglong Zhao; Han Wang; Zi Fu; Hongbo Gao; Weijun Peng; Dalong Ni; Wei Tang; Yajia Gu (Journal of Nanobiotechnology, 2022)
Abstract Contrast-enhanced MR angiography (MRA) is a critical technique for vascular imaging. Nevertheless, the efficacy of MRA is often limited by the low rate of relaxation, short blood-circulation time, and metal ion-released potential long-term toxicity of clinical available Gd-based contrast agents. In this work, we report a facile and efficient strategy to achieve Gd-chelated organic nanoparticles with high relaxivity for T 1 -weighted MRA imaging. The Gd-chelated PEG-TCPP nanoparticles (GPT NPs) have been engineered composite structured consisting of Gd-chelated TCPP and PEG. The spherical structure of TCPP offers more chemical sites for Gd3+ coordination to improve the relaxivity and avoid leakage of the Gd3+ ions. The synthesized GPT NPs exhibit a high relaxation rate of 35.76 mM− 1 s− 1 at 3.0 T, which is higher than the rates for most reported MR contrast agents. Therefore, GPT NPs can be used for MRA with much stronger vascular signals, longer circulation time, and high-resolution arterial vascular visualization than those using clinical MR contrast agents at the same dose. This work may make the T 1 MRI contrast agents for high-resolution angiography possible and offer a new candidate for preclinical and clinical applications of MR vascular imaging and vascular disease diagnosis. Graphical Abstract